Isolasi dan Identifikasi Bakteri Penyebab Bau Kaki - Renna Yulia Vernanda; Agnes Dwi Ariyanti; Claudia Oktaviana; Firman Sandi Gunawan; Yohana Maria Vianney Prastica; Flora Raliana Mauryn; Angelica Krisensiani Rati; Fridolin Putri Hasfayo; Margareta Vita Ribeiro (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2023)
Foot odour is caused by combination of sweat and bacteria. Smelly feet can lead to lack of confidence and discomfort. In this study, conducted on 21 probands to isolate the microbes with the following criteria: male, aged 18-25 years, wore shoes for 8 hours without taking them off, moist, and smelly feet. Isolating microbes from the feet using a cotton swab. The result of the study found 7 isolates. Several bacteria isolates, namely: Staphylococcus sp, Bacillus sp, Enterobacter sp. In addition, isolates from fungi Aspergillus sp, Penicillium sp, Syncephalastrum sp, and Candida krusei yeast were isolate